Long-term X-ray variability characteristics of the narrow-line Seyfert 1 galaxy RE J1034+396 - Chaudhury, K.; Chandra, S.; Chitnis, V.R.; Rao, A.R.; Singh, K.P. (Oxford Univ Press, 2018)
We present the results of our study of the long-term X-ray variability characteristics of the narrow-line Seyfert 1 galaxy RE J1034+396. We use data obtained from the AstroSat satellite along with light curves obtained from XMM-Newton and Swift-XRT. We use the 0.3-7.0 keV and 3-20 keV data, respectively, from the SXT and the LAXPC of AstroSat. The X-ray spectra in the 0.3-20 keV region are well fitted with a model consisting of a power law and a soft excess described by a thermal Compton emission with a large optical depth, consistent with the earlier reported results. We have examined the X-ray light curves in the soft and hard X-ray bands of the SXT and LAXPC, respectively, and find that the variability is slightly larger in the hard band. To investigate the variability characteristics of this source at different time-scales, we have used X-ray light curves obtained from XMM-Newton data (200 s to 100 ks range) and Swift-XRT data (1 to 100 d range) and find that there is evidence to suggest that the variability increases sharply at longer time-scales. We argue that the mass of the black hole in RE J1034+396 is likely to be ∼3 × 106 M⊙, based on the similarity of the observed quasi-periodic oscillation (QPO) to the high-frequency QPO seen in the galactic black hole binary GRS 1915+105
Keywords: Accretion; Accretion discs; Galaxies: active; Galaxies: individual: RE J1034+396; Galaxies: Seyfert; X-rays: galaxies